Effectiveness of Using Augmented Reality on the RHDP Platform in Supporting Reproductive Health Education - Saddiyah Rangkuti; Muslimah Pase; Niasty Lasmy Zaen (Indonesian Journal of Global Health Research, 2025)
Infertility is a crucial issue in reproductive health, impacting not only an individual's quality of life but also social, psychological, and cultural implications. Low reproductive health literacy in Indonesia, particularly in rural areas, poses a serious challenge in addressing this issue. This study aims to analyze the effectiveness of digital technology utilization through the Reproductive Health Digital Platform (RHDP) in improving reproductive health literacy in the Stabat District community, with a focus on infertility. A. total of 20 participants were involved in this study, selected using purposive sampling to ensure relevance to the research focus. The research method used a descriptive qualitative approach with data collection techniques through questionnaires, in-depth interviews, and focus group discussions (FGDs), supported by secondary data from official documents and scientific literature.. Data analysis was conducted using the Miles and Huberman interactive model with triangulation of methods and sources to maintain validity. The results show that the RHDP platform is effective in improving the quality of digital reproductive health services based on Pedrosa's eight effectiveness indicators. The dimensions with the highest scores are user trust in data security and information credibility, while the aspect with a relatively low score is system consistency across devices. These findings confirm that digital transformation plays a crucial role in expanding access and literacy in reproductive health, but strengthening infrastructure, regulations, and complaint management features is still needed to support service sustainability.